Upscaling the fabrication routine of bioreplicated rose petal light harvesting layers for photovoltaic modules. (1st May 2020) - Fritz, Benjamin; Hünig, Ruben; Guttmann, Markus; Schneider, Marc; Reza, K.M. Samaun; Salomon, Oliver; Jackson, Philip; Powalla, Michael; Lemmer, Uli; Gomard, Guillaume
Highlights: Development of an upscaled routine for the replication of plant surface microtextures. 100 cm 2 petal replicas laminated onto CIGS solar modules as light harvesting layers. Excellent light in-coupling properties demonstrated at incidence angles above 50°. Mean generated power increase of +5.4% measured under outdoor conditions over 41 days. Abstract: The hierarchical micro-/nanotextures adorning the petal surfaces of certain flower species exhibit outstanding sunlight harvesting properties, which can be exploited for photovoltaic (PV) applications via a direct replication approach into polymeric cover layers. This route has been so far hampered by the restricted size of the original bio-template and by the limited number of replication cycles when a polymeric mold is used. Here, we therefore introduce an upscaling strategy allowing the fabrication of mechanically stable, temperature resistant and large area nickel mold inserts which can be employed for hot embossing lithography, and ultimately for the mass production of bioreplicated films that improve light management in PV modules. As a proof-of-concept, we laminate the thus produced textured foils, here corresponding to rose petal replicas, onto glass encapsulated copper indium gallium diselenide (CIGS) solar modules with a surface of 100 cm 2 . We demonstrate an increase of the power output of 5.4% with respect to a device with an uncoated glass cover layer (measured in outdoor operating conditions). This improvement is notably attributed to the excellent light in-coupling properties of the replicated texture at high oblique incidence angles.